(untitled) (diségno, 2021)
For almost 20 years, several events have radically, and in our opinion permanently, changed the scientific publishing. For example, in 1997 was born Web of Science [1]; in 1999 starts Open Access Initiative [2]; in 2002 was signed the Budapest Open Access Initiative [3], followed in 2003 by Berlin Declaration on Open Access to Knowledge in the Sciences and Humanities [4] and in 2004 by the Dichiarazione di Messina [5]; also in 2004, Elsevier made Scopus available online [6] (read more).